1992
DOI: 10.1007/bf00196867
|View full text |Cite
|
Sign up to set email alerts
|

Dormant bacteria in lake sediments as palaeoecological indicators

Abstract: Lake sediments contain viable allochthonous bacteria that can be cultured and used for palaeoecological studies. To be a good palaeoindicator, a bacterium must be able to survive in sediments for long periods of time, but also be unable to reproduce in the lake bottom. Bacteria can survive the unfavourable environmental conditions in lake sediments as resting cells. The endospore is the most specialized form and gives the bacterium an extreme longevity. The oldest viable endospores isolated from lake sediments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This is a phenomenon that has, for instance, been explored in diatoms or zooplankton where cells or egg banks in the sediments can be used to track effects of environmental change on lake ecosystems (Smol, ). Whereas diatoms and zooplankton species occur in sediments as fossils, it has been shown for bacteria that sediments contain both dormant cells (Renberg and Nilsson, ; Lomstein et al ., ; Wunderlin et al ., ) and slow growing vegetative cells (Parkes et al ., ; Schippers et al ., ; Lomstein et al ., ). The detection of vegetative cells in deeper sediment layers suggests that ancient bacteria, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This is a phenomenon that has, for instance, been explored in diatoms or zooplankton where cells or egg banks in the sediments can be used to track effects of environmental change on lake ecosystems (Smol, ). Whereas diatoms and zooplankton species occur in sediments as fossils, it has been shown for bacteria that sediments contain both dormant cells (Renberg and Nilsson, ; Lomstein et al ., ; Wunderlin et al ., ) and slow growing vegetative cells (Parkes et al ., ; Schippers et al ., ; Lomstein et al ., ). The detection of vegetative cells in deeper sediment layers suggests that ancient bacteria, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This might be the case for bacterial endospores, highly resistant cellular forms produced by certain genera belonging to the Firmicutes (Gram-positive low G?C content bacteria) (Onyenwoke et al 2004), which are able to survive in a dormant state, with little to no in situ activity, for a long period of time. The potential of dormant bacteria to be used as paleoecological indicators was evaluated by Renberg and Nilsson (1992). They concluded that it was possible to isolate dormant bacteria (Thermoactinomyces spp., Bacilli and Clostridia endospores) from sediment and, by combining the analysis of biochemical and genetic data, to infer past environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…in archeological excavations containing plant debris deposited between 85 and 125 AD (Seaward et al 1976). Spores are commonly found in sediments and isolation and enumeration of viable cells and spores from sedimentary archives is an old technique (Renberg and Nilsson 1992). Viable endospores have been isolated from 5,800-year-old (Bartholomew and Paik 1966) and 9,000-year-old lake sediments (Renberg and Nilsson 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Midges are particularly good indicators of environmental conditions because the species respond quickly to environmental changes and are particularly sensitive to water quality, including the amount of oxygen in the water. Dormant bacteria can be useful paleoindicators for the influence of sewage and of agricultural activity upon lakes (Renberg and Nilsson 1992).…”
Section: Questions Of Scalementioning
confidence: 99%